Dynamics of mRNA and polysomal abundance in early 3T3-L1 adipogenesis - von der Heyde, Silvia (BioMed Central, 2014)
BACKGROUND: Adipogenesis is a complex process, in which immature pre-adipocytes change morphology, micro-anatomy and physiology to become mature adipocytes. These store and accumulate fat and release diverse hormones. Massive changes in protein content and protein composition of the transforming cell take place within a short time-frame. In a previous study we analyzed changes in the abundance of free and polysomal, i.e. ribosome bound, RNAs in the first hours of adipogenesis in the murine cell line 3T3-L1. Here we analyze changes of mRNA levels and their potential contribution to the changing protein pool by determination of mRNA levels and ribosome binding to mRNAs in 3T3-L1 cells stimulated for adipogenesis. We grouped mRNA species into categories with respect to up- or down-regulated transcription and translation and analyzed the groups regarding specific functionalities based on Gene Ontology (GO). RESULTS: A shift towards up-regulation of gene expression in early adipogenesis was detected. Genes up-regulated at the transcriptional (TC:up) and translational (TL:up) level (TC:up/TL:up) are very likely involved in control and logistics of translation. Many of them are known to contain a TOP motif. In the TC:up/TL:unchanged group we detected most of the metal binding proteins and metal transporters. In the TC:unchanged/TL:up group several factors of the olfactory receptor family were identified, while in TC:unchanged/TL:down methylation and repair genes are represented. In the TC:down/TL:up group we detected many signaling factors. The TC:down/TL:unchanged group mainly consists of regulatory factors. CONCLUSIONS: Within the first hours of adipogenesis, changes in transcriptional and translational regulation take place. Notably, genes with a specific biological or molecular function tend to cluster in groups according to their transcriptional and translational regulation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-381) contains supplementary material, which is available to authorized users.